Expression of SASH1 in Preeclampsia and Its Effects on Human Trophoblast - Yu, Yanhong; Huang, Liping; Jiang, Sijia; Liu, Shisan (BioMed research international, 2020)
Aim. To explore the involvement of SASH1 in preeclampsia. Methods. Expression of SASH1 was determined by qPCR, WB, and immunohistochemistry in the placenta of both normal and preeclamptic pregnancies. The SASH1 gene of human HTR-8/SVneo cells was overexpressed by transfection of pEZ-Lv206-SASH1. After that, the CCK-8 assay, EdU assay, transwell assay, and flow cytometry were used to examine the cell proliferation, migration, invasion, and apoptosis. Results. Higher expression of SASH1 was detected in placental tissues collected from patients with preeclampsia, compared with those from gestational age-matched control samples. The expression of SASH1 was significantly enhanced by transfection with pEZ-Lv206-SASH1 in HTR-8/SVneo cells. In addition, the HTR-8/SVneo cells transfected with pEZ-Lv206-SASH1 exhibited significantly reduced proliferation, migration, and invasion ability compared to the cells in the empty vector group and normal group. Flow cytometry analysis demonstrated that the apoptosis rate of cells transfected with pEZ-Lv206-SASH1 was significantly higher than that of cells transfected with empty vector and untreated cells. Conclusions. SASH1 is significantly upregulated in the placenta of preeclampsia, and overexpression of SASH1 can inhibit the proliferation, migration, and invasion, but induce apoptosis of trophoblast cells in vitro.